BAHASA MELAYU: ANTARA PELUASAN, PENYEMPITAN DAN KECELARUAN - Abd. Rahman, Azlinda (Journal of Techno-Social, 2013)
Civilization of a particular race developed from its language. The development of a language in a racial community is correlated with its association with the establishment a country. Also, as a language which is included in the modernization and expanding throughout the world, Malay language is not an exception from facing the changes, construction and disorder. Changes and construction in here including expansion of meaning, narrowing of meaning and diction absorption that sometimes may cause confusion and reducing the quality of the usage of the language itself. Due to the expansion with the other languages, Malay language has experienced language soundsborrowing process from the other languages. These language sounds were borrowed to accommodate the incoming of many borrowed word forms to enrich the grammatical aspects in Malay language. The influence was engaged through several mediums that cause the language and dialects mixture among the confused speakers and this is a linguistics phenomena. Three top recognitions were given to Malay language including Malay language as a national, official and wisdom language. Civilization of a languageincreases depending on the language that is acknowledged as a wisdom language with the existence of expansion and narrowing of meaning meanwhile confusion is closely related to the diction that experience the borrowing process but awkward in the usage of the language. The implications are closely related to the development and the brokenlanguage as what has been imparted.